Infliximab-Induced Acute Liver Failure in a Patient With Crohn's Disease Requiring Orthotopic Liver Transplantation. Issue 5 (14th May 2021) - Mustafa Alikhan, Muhammed; Mansoor, Emad; Satyavada, Sagarika; Greer, Katarina; Xin, Wei; Cohen, Stanley; Cooper, Gregory; Katz, Jeffry
ABSTRACT: Tumor necrosis factor-alpha inhibitors are not known to have significant liver toxicity; however, a few case reports state otherwise. We report the case of a 25-year-old man with Crohn's disease who was initiated on infliximab. The patient developed severe mixed hepatocellular and cholestatic liver injury that progressed into acute liver failure. Based on clinical history, laboratory findings, and histology, this was presumed because of the development of autoimmune hepatitis secondary to infliximab. He underwent liver transplantation. The mainstay of treatment in this rare condition involves steroid therapy and possible transplantation. Patients must then avoid anti–tumor necrosis factor-alpha therapy for life.